A Postmarketing Surveillance Study on Erbitux (Cetuximab) in Patients with Metastatic Colorectal Cancer Refractory to Irinotecan-Containing Treatment. (October 2013) - Huang, Wen-Tsung; Chen, Hong-Hwa; Yeh, Chung-Hung; Lu, Yin-Che; Hwang, Wei-Shou; Huang, Jen-Seng; Chen, Chou-Pin; Lin, Peng-Chan; Uen, Wu-Ching; Lee, Yang-Cheng; Wang, Hwei-Ming; Wu, Hong-Cheng; et al.
Objective: This postmarketing surveillance study evaluated the safety and efficacy of cetuximab therapy in patients with epidermal growth factor receptor (EGFR)-expressing metastatic colorectal cancer (mCRC) in Taiwan. Methods: Patients with EGFR-expressing mCRC who had failed prior irinotecan-based chemotherapy and were receiving cetuximab therapy were monitored for treatment efficacy and safety from the time of first infusion until 28 days after the last infusion regardless of the reasons fordiscontinuation. The study followed 269 patients for approximately 2years. Results: No unexpected adverse events associated with cetuximab therapy were reported, and most events were grade 1 or 2. The most common drug-related adverse events of any grade were rash (21.6%) and dermatitis acneiform (4.8%). Reported grade 3/4 events were rash (4.5%), dermatitis acneiform (0.4%), and diarrhea (0.4%). Cetuximab treatment for patients receiving second-/third-line (177 patients) or above therapy (92 patients) was associated with a median progression-free survival time of 3.37 and 3.90 months, respectively, and a median overall survival time of 17.6 and 21.1 months, respectively. The response rates for the second-/third-line treatment and fourth-line or above cetuximab treatment groups were similar (21.5% vs 17.4%; P = 0.428). Conclusion: Cetuximab showed no unexpected safety findings and was efficacious in treating patients with EGFR-expressing mCRC in community practice in Taiwan.